Bauddha-darśana-mīmāṃsā : Bauddha-dharma tathā tattvajñāna kā saṅgopāṅga prāñjala prāmāṇika vivecana - Upadhyaya, Baldeva, 1899- (SAMP early 20th-century Indian books project, 1954)
Buddhist philosophy.